Comparative Analysis of the Effectiveness of Lectures and Video-Assisted Learning in Improving Learning Outcomes of Students at TK Perjuangan in Bengkulu City - Intan Permata Sari; Adamu Abubakar Muhammad; Johanes Sapri (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
Background of study: The main factor behind this research is the changing characteristics and learning style needs of Generation Alpha, today's kindergarten students. To create a fun, meaningful, and conscious learning environment, schools and teachers must incorporate digital technologies such as smart TVs or interactive large screen panels into their learning processes. Video-assisted learning (VAL) is considered attractive because it can make learning easier for kindergarten-aged children to understand and enjoy.Aims: The purpose of this study was to evaluate the effectiveness of conventional lectures compared to video-assisted learning in improving student learning outcomes at Perjuangan Kindergarten in Bengkulu City.Methods: This study used an experimental method with a sample of fifteen students from Class B1 and fifteen students from Class B2, each of whom received different treatments. Pre-tests and post-tests with pictures tailored to aspects of child development were used to assess learning outcomes. To conclude the effectiveness of the two methods, the data were tested with N-Gain scores using SPSS.Result: Students in classes taught using the VAL method obtained an N-Gain score of 68.5%, indicating that this method is quite effective in improving their learning outcomes. Students in classes taught using the lecture method only obtained an N-Gain score of 26.9%, indicating that this method is not effective in improving student learning outcomes. This study shows a significant difference between the two methods.Conclusion: This study concluded that the Video Assisted Learning method was more effective in improving student learning outcomes than the lecture method.